2011
DOI: 10.3138/ptc.2010-29
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Falls Efficacy and Improvement in Fall Risk Factors Following an Exercise Plus Educational Intervention for Older Adults with Hip Osteoarthritis

Abstract: Purpose: Older adults with decreased confidence in their ability to prevent a fall may benefit from an exercise programme that includes self-efficacyenhancing education. The objectives of this study were to explore differences in fall-risk outcomes in older adults with higher vs. lower levels of falls efficacy and to evaluate the relationship between baseline falls-efficacy status and changes in fall risk factors following two interventions. Method: Fifty-four older adults with hip osteoarthritis and at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 47 publications
(63 reference statements)
0
22
0
10
Order By: Relevance
“…This idea that physical capacity alone does not predict activity and participation post-stroke was shown in a study by Schmid et al 35 which found that self-efficacy impacts self-reported activity and participation in persons post stroke. 9 The impact of self-efficacy on activity and participation has also been shown in community dwelling manual wheelchair users aged 50 years or older 36 , individuals with hip osteoarthritis 37 , adults with arthritis 38 and women with fibromyalgia. 39 Research in other populations, including spinal cord injury, congestive heart failure, and knee osteoarthritis, also supports the role of self-efficacy as a mediator between performance and activity and participation domains.…”
Section: Discussionmentioning
confidence: 98%
“…This idea that physical capacity alone does not predict activity and participation post-stroke was shown in a study by Schmid et al 35 which found that self-efficacy impacts self-reported activity and participation in persons post stroke. 9 The impact of self-efficacy on activity and participation has also been shown in community dwelling manual wheelchair users aged 50 years or older 36 , individuals with hip osteoarthritis 37 , adults with arthritis 38 and women with fibromyalgia. 39 Research in other populations, including spinal cord injury, congestive heart failure, and knee osteoarthritis, also supports the role of self-efficacy as a mediator between performance and activity and participation domains.…”
Section: Discussionmentioning
confidence: 98%
“…22 In addition, older adults with hip OA and lower levels of falls efficacy responded better (i.e., with better physical performance and increases in falls efficacy) than those with higher levels of falls efficacy when education was combined with exercise. 23 Taken together, these findings suggest that older adults with hip OA are at an increased risk of falls as a result of combinations of physical and psychological fall-risk factors, and that interventions designed to address both types of factors should result in the greatest reduction of fall risk.…”
Section: Relationship Of Pain and Falls-efficacy To Balance And Walkingmentioning
confidence: 89%
“…6,7,[9][10][11][12][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Although all 21 studies included adults with OA or joint pain (including hip and knee), only 14 were specific to either hip or knee OA. 10,11,12,16,19,[20][21][22][23][25][26][27][28][29] We found few studies that addressed the relationship between personal and environmental contextual factors and fall risk spe- Adapted from the Summary of the updated American Geriatrics Society/British Geriatrics Society clinical practice guideline for prevention of falls in older persons. BBS: Berg Balance Scale; TUG: timed up-and-go Test; ABC: Activities-specific Balance Confidence.…”
Section: Methodsmentioning
confidence: 99%
“…Four studies specifically used motivational interviewing (MI) as a main interventional strategy (Arkkukangas, Soderlund, Eriksson, & Johansson, ; Dorresteijn et al, ; Szanton et al, ). Seven studies used a small‐group‐based setting for their CBT‐based component, with group sizes ranging from 4–15 people (Arnold et al, ; Clemson et al, ; Freiberger et al, , ; Liu & Tsui, ; Tennstedt et al, ; Zijlstra et al, ). All study interventions included an exercise component in conjunction with CBT‐based strategies except for two studies.…”
Section: Resultsmentioning
confidence: 99%